Pomegranate juice fermented by tannin acyl hydrolase and Lactobacillus vespulae DCY75 enhance estrogen receptor expression and anti-inflammatory effect - Akter, Reshmi; Chan Ahn, Jong; Nahar, Jinnatun; Awais, Muhammad; Ramadhania, Zelika Mega; Oh, Se-Woung; Oh, Ji-Hyung; Kong, Byoung Man; Rupa, Esrat Jahan; Lee, Dong Wong; Yang, Deok Chun; Chan kang, Se (Frontiers in Pharmacology, 2022)
Phenolics are extensively distributed phytochemicals primarily found in plants, including fruits and vegetables. They have potential biological activities and health-promoting efficacy. To increase the phenolic contents and their nutritional values, fermentation is one of the most readily used methods in the food industry. Active substances in Pomegranate (PG) juice are mostly present as precursors. These functional precursors must be converted into a glassy state for fast absorption. This study aims to restore active pomegranate precursors by fermentation using Tannin acyl hydrolase and Lactobacillus vespulae DCY75 and enhance the ellagic acid content, respectively to investigate the effect of Pomegranate on ERα and ERβ mRNA expression along with NO inhibition. To study estrogen-like activity, we used breast cancer cell line MCF-7, which has high ERα expression, and RAW 264.7 cells for studying post-menopausal inflammation. The mRNA expression of ERα, ERβ, and pS2 was analyzed to detect estrogen-like activity. Furthermore, anti-inflammatory effect was investigated by measuring NO/iNOS inhibition. The cell proliferation has been increased by fermented Pomegranate (PG-F) juice in MCF7 cells while there was no specific toxicity noticed in RAW 264.7 cells. The mRNA expression of all of the genes (ERα, ERβ, and pS2) upregulated with the PG juice treatment, whereas fermented Pomegranate (PG-F) juice showed better expression than unfermented Pomegranate juice. Furthermore, fermented pomegranate sample has remarkably inhibited NO production as well as iNOS, key enzymes generating nitric oxide (NO) which indicates the anti-inflammatory potential of PG-F. To sum it up, we fermented the commercial Pomegranate juice to increase the amount of ellagic acid which significantly increases the estrogen-like activity and reduced the risk of post-menopausal inflammation